Effects of a virtual reality-based mirror therapy system on upper extremity rehabilitation after stroke: a systematic review and meta-analysis of randomized controlled trials - Okamura, Ryohei; Nakashima, Akira; Moriuchi, Takefumi; Fujiwara, Kengo; Ohno, Kanta; Higashi, Toshio; Tomori, Kounosuke (Frontiers in Neurology, 2024)
Introduction: Virtual Reality-based Mirror Therapy (VRMT) has recently attracted attention as a novel and promising approach for treating upper extremity dysfunction in patients with stroke. However, the clinical efficacy of VRMT has not been investigated. Methods: This study aimed to conduct a meta-analysis to evaluate the effects of VRMT on upper extremity dysfunction in patients with stroke. We screened articles published between January 2010 and July 2022 in PubMed, Scopus, MEDLINE, and Cochrane Central Register of Controlled Trials. Our inclusion criteria focused on randomized controlled trials (RCTs) comparing VRMT groups with control groups (e.g., conventional mirror therapy, occupational therapy, physical therapy, or sham therapy). The outcome measures included the Fugl-Meyer assessment upper extremity test (FMA-UE), the Box and Block Test (BBT), and the manual function test (MFT). Risk of bias was assessed using the Cochrane Collaboration risk-of-bias tool 2.0. We calculated the standardized mean differences (SMD) and 95% confidence intervals (95% CI). The experimental protocol was registered in the PROSPERO database (CRD42022345756). Results: This study included five RCTs with 148 stroke patients. The metaanalysis showed statistical differences in the results of FMA-UE (SMD = 0.81, 95% CI [0.52, 1.10], p<0.001), BBT (SMD = 0.48, 95% CI [0.16, 0.80], p=0.003), and MFT (SMD = 0.72, 95% CI [0.05, 1.40], p=0.04) between the VRMT and the control groups. Discussion: VRMT may play a beneficial role in improving upper extremity dysfunction after stroke, especially when combined with conventional rehabilitation. However, there were differences in the type of VRMT, stage of disease, and severity of upper extremity dysfunction. Multiple reports of high-quality RCTs are needed to clarify the effects of VRMT.